2018
DOI: 10.4110/in.2018.18.e32
|View full text |Cite
|
Sign up to set email alerts
|

Viperin Deficiency Promotes Polarization of Macrophages and Secretion of M1 and M2 Cytokines

Abstract: Viperin is a multifunctional protein that was first identified in human primary macrophages treated with interferon-γ and in human fibroblasts infected with human cytomegalovirus. This protein plays a role as an anti-viral protein and a regulator of cell signaling pathways or cellular metabolism when induced in a variety of cells such as fibroblasts, hepatocytes and immune cells including T cells and dendritic cells. However, the role of viperin in macrophages is unknown. Here, we show that viperin is basally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…This T-cell polarization identified as IFNγ-producing Th1 (Fig 3), could be a result of the increased stimulation potential of Viperin −/− APCs via soluble mediators after viral stimulation (Figs 4 and 5, and S8). Consistent with this, it was recently shown in vitro that mice BMDM deficient for Viperin were more polarized to either M1 or M2 and had enhanced secretion of immune mediators upon stimulation (Eom et al, 2018). Similarly, Viperin −/− was shown to be necessary for inhibition of type I IFN production in macrophages (Hee & Cresswell, 2017).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This T-cell polarization identified as IFNγ-producing Th1 (Fig 3), could be a result of the increased stimulation potential of Viperin −/− APCs via soluble mediators after viral stimulation (Figs 4 and 5, and S8). Consistent with this, it was recently shown in vitro that mice BMDM deficient for Viperin were more polarized to either M1 or M2 and had enhanced secretion of immune mediators upon stimulation (Eom et al, 2018). Similarly, Viperin −/− was shown to be necessary for inhibition of type I IFN production in macrophages (Hee & Cresswell, 2017).…”
Section: Discussionsupporting
confidence: 58%
“…Notably, Viperin enzymatic function was recently shown to be a convertase of CTP in 3′-deoxy-3′,4′-didehydro-CTP (ddhCTP) which was also reported to have chain reaction termination properties on RNA polymerase of flaviviruses (Gizzi et al, 2018). Our results, taken together with the observed phenotypes of Viperin −/− on macrophage polarization and cytokine production (Eom et al, 2018), interferon response signaling (Hee & Cresswell, 2017), and TLR-7/9 signaling pathway (Jiang & Chen, 2011; Saitoh et al, 2011), raise very intriguing questions on the main role of Viperin during immune responses. Is the enzymatic activity of Viperin linked to these immune regulatory functions, which would imply a role of CTP or ddhCTP in immune signaling and/or polarization, or are Viperin functions on immune responses unrelated to this enzymatic activity but rather to other Viperin protein partners because the SAM domain of Viperin is dispensable for flavivirus restriction (Helbig et al, 2011, 2013)?…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, based on available data regarding the antiviral activity of RSAD2, different mechanisms can be postulated: (i) it is shown that the intracellular NAD + levels modulate TNF‐α protein synthesis [42]. It is known that TNF has antiviral activity [43–45], and it is observed that expression of TNF‐α in RSAD2‐KO cells decreases approximately two‐fold [46]. These data together with our findings suggest that ddhCTP inhibits the NAD + ‐dependent reactions to modulate the cellular level of TNF‐α and restrict viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, including IL-10 and IL-13, from immune cells such as macrophages and eosinophils reportedly regulate thermogenesis in adipose tissues (33)(34)(35). We recently showed that viperin deficiency promotes the secretion of proinflammatory and antiinflammatory cytokines from completely differentiated bone marrow-derived macrophages (36). However, viperin was not detected in macrophages in the BAT of mice fed RC.…”
Section: Viperin Deficiency Promotes Thermogenic Gene Expression In Amentioning
confidence: 99%